THE PROHIBITION OF USURY (RIBA) A MORAL-ETHICAL PERSPECTIVE OF ISLAMIC FINANCIAL AND BANKING LAW: A COMPARATIVE STUDY BETWEEN THE ISLAMIC AND THE CONVENTIONAL MODEL - P. Swartz, Nico (Jurnal Syariah, 2009)
We live in a world which has for all practical purposes, abandoned religious foundations in its economic systems. In our troubled world – some of the gravest problems we face is global warming, a food crisis and poverty – there is a need to return to the Revelation of Harmony and human reason in our economic thinking. Both the socialist as well as the capitalist in the economic systems have proven their failure to ensure economic justice that serves to benefit all in the society, both the rich and the poor. In particular, capitalism is currently causing a terrifying scenario by making the rich richer and the poor poorer. In this context, the fundamental motivation for this research is to examine whether a Divinely inspired banking system could contribute to alleviating the global financial crisis that we are facing. In fact, it has been remarked that the Islamic economic system represents a via media between socialism and capitalism. Of course, the prohibition of interest/usury rests on an ethical foundation. It is necessary to reassert that this banking ethic is based on the avoidance of all form of financial exploitation and having as its principal objective to combine the purpose of wealth creation and poverty alleviation.